Whole genome sequences of Treponema pallidum subsp. endemicum isolated from Cuban patients: The non-clonal character of isolates suggests a persistent human infection rather than a single outbreak - Vrbová, Eliška; Noda, Angel A; Grillová, Linda; Rodríguez, Islay; Forsyth, Allyn; Oppelt, Jan; Šmajs, David (PLoS neglected tropical diseases, 2022)
Bejel (endemic syphilis) is a neglected non-venereal disease caused by Treponema pallidum subsp. endemicum (TEN). Although it is mostly present in hot, dry climates, a few cases have been found outside of these areas. The aim of this work was the sequencing and analysis of TEN isolates obtained from "syphilis patients" in Cuba, which is not considered an endemic area for bejel. Genomes were obtained by pool segment genome sequencing or direct sequencing methods, and the bioinformatics analysis was performed according to an established pipeline. We obtained four genomes with 100%, 81.7%, 52.6%, and 21.1% breadth of coverage, respectively. The sequenced genomes revealed a non-clonal character, with nucleotide variability ranging between 0.2-10.3 nucleotide substitutions per 100 kbp among the TEN isolates. Nucleotide changes affected 27 genes, and the analysis of the completely sequenced genome also showed a recombination event between tprC and tprI, in TP0488 as well as in the intergenic region between TP0127-TP0129. Despite limitations in the quality of samples affecting breadth of sequencing coverage, the determined non-clonal character of the isolates suggests a persistent infection in the Cuban population rather than a single outbreak caused by imported case.
Keywords: Syphilis; Disease Outbreaks; Treponema; Treponema pallidum; Humans; syfilis; lidé; epidemický výskyt choroby; Treponemal Infections; nukleotidy; infekce bakteriemi rodu Treponema; Nucleotides